A 137‐kb deletion within the Potocki–Shaffer syndrome interval on chromosome 11p11.2 associated with developmental delay and hypotonia123. Issue 1 (13th December 2012) - Montgomery, Nathan D.; Turcott, Christie M.; Tepperberg, James H.; McDonald, Marie T.; Aylsworth, Arthur S.
Abstract Potocki–Shaffer syndrome (PSS) is a rare disorder caused by haploinsufficiency of genes located on the proximal short arm of chromosome 11 (11p11.2p12). Classic features include biparietal foramina, multiple exostoses, profound hypotonia, dysmorphic features, and developmental delay/intellectual disability. Fewer than 40 individuals with PSS have been reported, with variable clinical presentations due in part to disparity in deletion sizes. We report on a boy who presented for initial evaluation at age 13 months because of a history of developmental delay, hypotonia, subtle dysmorphic features, and neurobehavioral abnormalities. SNP microarray analysis identified a 137 kb deletion at 11p11.2, which maps within the classically defined PSS interval. This deletion results in haploinsufficiency for all or portions of six OMIM genes: SLC35C1, CRY2, MAPK8IP1, PEX16, GYLTL1B, and PHF21A. Recently, translocations interrupting PHF21A have been associated with intellectual disability and craniofacial anomalies similar to those seen in PSS. The identification of this small deletion in a child with developmental delay and hypotonia provides further evidence for the genetic basis of developmental disability and identifies a critical region sufficient to cause hypotonia in this syndrome. Additionally, this case illustrates the utility of high resolution genomic approaches in correlating clinical phenotypes with specific genes in contiguous gene deletion syndromes. © 2012 Wiley Periodicals, Inc.